Improving Fourth-Grade Students' Learning Outcomes in Science and Social Studies Through Numbered Heads Together - Siti Kurnia; Nashrullah Nashrullah; Muslim AR Muslim AR; Abdul Rahman; Sri Wahyuni; Surahman Wilade (Journal of Innovation and Research in Primary Education, 2026)
Persistent challenges in elementary science education, including teacher-centered pedagogy, low student engagement, and inadequate learning outcomes, necessitate pedagogical innovations that promote active participation and conceptual understanding. This classroom action research investigated the effectiveness of the Numbered Heads Together (NHT) cooperative learning model in enhancing fourth-grade students' learning outcomes in Science and Social Studies (IPAS) at SD Inpres Perumnas Palu. Twenty-eight students participated in two iterative cycles comprising planning, implementation, observation, and reflection phases. Data were collected through achievement tests, structured observation sheets for teacher and student activities, and field documentation, analyzed using both quantitative and qualitative methods. Findings demonstrated progressive improvements across all measured variables. Teacher activity increased from good (68-73%) in Cycle I to very good (92-95%) in Cycle II. Student engagement advanced from adequate (61-63%) to very good (80-81%). Most significantly, classical mastery rose from 33% at baseline to 43% in Cycle I and 79% in Cycle II, surpassing the 65% success criterion. Results confirm that NHT effectively transforms passive learning environments into active collaborative spaces, supporting both cognitive achievement and social-emotional development. The structured accountability mechanisms inherent in NHT promote equitable participation and peer-mediated learning consistent with social constructivist principles, demonstrating applicability in resource-limited settings with diverse student populations.